A copper nanoparticle catalyst and its preparation method and application

By using copper nanoparticle catalyst and carbon material substrate, combined with oleamine oleic acid reduction method, high-efficiency electrocatalytic reduction from nitrogen monoxide to ammonia is achieved, solving the problem of difficult process kinetics of nitrogen as a nitrogen source in the prior art, and achieving efficient and economical ammonia production.

CN115928129BActive Publication Date: 2025-03-18YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211545069.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-21
Publication Date
2025-03-18
Estimated Expiration
2042-11-21

AI Technical Summary

Technical Problem

At this stage, the kinetics of the electrocatalytic synthesis process with nitrogen as the nitrogen source are difficult to carry out, the kinetics of nitrogen hydrogenation reaction are poor, and the Faraday efficiency of ammonia is low, making it difficult to replace the Haber-Bosch method for large-scale artificial synthesis of NH3.

Method used

The copper nanoparticle catalyst is prepared by oleamine oleic acid reduction method, combined with a carbon material substrate to achieve single selective electrocatalytic reduction from nitric oxide to ammonia.

Benefits of technology

It realizes high-efficiency electrocatalytic reduction from nitrogen monoxide to ammonia, the Faraday efficiency of ammonia gas reaches 94.78%, and the ammonia production rate is 396.9μmol cm-2h-1. It has a large cost advantage and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115928129B_ABST
    Figure CN115928129B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a copper nanoparticle catalyst and its application. The copper metal nanocatalyst is in the form of dispersed particles. The preparation thereof comprises the following steps: heating copper salt, oleylamine and oleic acid at 20 to 60 degrees Celsius under nitrogen or other inert atmosphere, stirring and uniformly mixing, heating to 160 to 220 degrees Celsius at a certain rate for full reaction for 2 to 4 hours, obtaining a mixture of copper particles and other reaction products, cooling, centrifuging, washing and drying to obtain nanostructured copper particles. The copper nanoparticle catalyst obtained by the present invention can be applied to the electrocatalytic reaction of reducing nitric oxide to produce ammonia. Through the structural design of the catalyst copper, the nanometer size of the catalyst copper increases the specific surface area of ​​the electrode, promotes the diffusion of nitric oxide and ammonia, and achieves a high catalytic rate and single selectivity of nitric oxide to ammonia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal catalysts and provides a copper nanoparticle catalyst and a preparation method and application thereof. Background Art

[0002] In the field of industrial ammonia synthesis, the traditional Haber-Bosch process has always been dominant, but this method needs to be operated under high temperature and high pressure conditions. The whole process consumes a lot of energy and emits a lot of carbon dioxide. Therefore, it is of great significance to develop a green, low-energy sustainable ammonia synthesis process. The electrocatalytic ammonia synthesis process has the advantages of being green, energy-saving, carbon-free, and sustainable. However, the current research hotspots are mainly focused on systems with nitrogen as the nitrogen source. Due to the poor proton affinity of inert nitrogen molecules, the molecules have no dipole moment, the polarizability is very low, and the dissociation energy is very high. It is difficult to be activated and cracked, resulting in the kinetic difficulty of the hydrogenation reaction of nitrogen. In addition, the hydrogen evolution reaction often has an advantage in kinetics, forming a fierce competition with nitrogen reduction. Most nitrogen reduction systems have a Faraday efficiency of less than 30% and a yield of less than 10 μmol cm -2 h -1 Therefore, the electrochemical ammonia synthesis process using nitrogen as a nitrogen source has almost no prospect of replacing the Haber-Bosch process for large-scale artificial synthesis of NH3. Therefore, it is urgent to develop other alternative technologies to achieve the goal of green and sustainable industrial synthesis of NH3.

[0003] Compared with the system with nitrogen as the nitrogen source, the dissociation energy of nitrogen in nitric oxide is much lower than that of non-polar molecular nitrogen, and nitric oxide is one of the main pollutants causing photochemical smog. Therefore, using nitric oxide as a nitrogen source to directly reduce it to ammonia can transform pollutants into high added value, which has good economic prospects.

[0004] However, there are few studies on the reduction of nitric oxide to ammonia. At present, the electrocatalysts used in the electrochemical reduction of nitric oxide to ammonia are mainly precious metals, transition metals and their compounds. Precious metals have the advantages of strong chemical stability, electrical conductivity and high electron cloud density, making them a highly active electrocatalyst, but their high price and limited natural resources limit their large-scale application; many transition metals not only have unique d electron orbits and controllable electronic structures, but also have the advantages of abundant resources and environmental friendliness, making them electrocatalyst materials with greater potential for industrial application. Therefore, the search for transition metal catalysts with high conversion efficiency and ammonia production rate and their structural optimization plays an important role in promoting the industrial development of nitric oxide reduction to ammonia. Summary of the invention

[0005] In this technical background, the technical problem to be solved by the present invention is to provide a copper nanoparticle catalyst and a preparation method and application thereof, so as to realize the single selective electrocatalytic reduction of nitric oxide to ammonia. The preparation method is convenient, the reaction conditions are mild, and it has a great cost advantage, which is conducive to large-scale industrial application.

[0006] To achieve the above invention objectives, the technical solution of the present invention is as follows:

[0007] The invention provides a copper nanoparticle catalyst, which is in the form of dispersed particles and has a particle size of nanocrystals of 20 to 100 nanometers.

[0008] The present invention provides a method for preparing a copper nanoparticle catalyst, comprising the following steps:

[0009] Step 1: After mixing the copper source, oleylamine and oleic acid, heat and stir at 20 to 60 degrees Celsius for 20 to 40 minutes under nitrogen or inert atmosphere to mix evenly;

[0010] Step 2: heating the mixed solution to 160-220 degrees Celsius at a certain rate under nitrogen or inert atmosphere, and fully reacting for 2-4 hours under magnetic stirring to obtain a mixture of copper particles and other reaction products;

[0011] Step 3: After the mixed solution is allowed to stand and cool, a solvent is added, the mixture is centrifuged, washed, and dried to obtain nanostructured copper particles;

[0012] Step 4: adding a solvent and a perfluorosulfonic acid polymer solution, ultrasonicating the mixed solution, spraying the solution evenly on the carbon material with a spray gun, and obtaining a copper nanoparticle catalyst based on the carbon material after drying.

[0013] As a preferred embodiment, the copper source includes but is not limited to one or more of copper acetate, copper sulfate, copper acetylacetonate, copper carbonate and basic copper carbonate.

[0014] As a preferred embodiment, the molar ratio of the copper source, oleylamine and oleic acid is 1:(120-140):(12-14), and the magnetic stirring rate is 500-700 revolutions per minute.

[0015] As a preferred embodiment, the heating rate in step 2 is 1 to 4 degrees Celsius per minute.

[0016] As a preferred embodiment, the magnetic stirring rate in step 2 is 500 to 700 revolutions per minute.

[0017] As a preferred embodiment, the solvent added in step 3 is one or more of n-hexane, cyclohexane, n-pentane and benzene, and the volume ratio of the reaction product to the solvent is 1:3.

[0018] As a preferred embodiment, in step 3, the number of centrifugation is 2 to 6 times, the centrifugal speed is 8000 to 12000 revolutions per minute, and the centrifugal time is 6 to 10 minutes.

[0019] As a preferred embodiment, the carbon material in step 4 is one of carbon cloth and carbon paper.

[0020] As a preferred embodiment, the solvent in step 4 is one or more of deionized water, methanol, ethanol, and isopropanol; the mass ratio of the catalyst to the solvent is 1:(50-70), and the volume ratio of the perfluorosulfonic acid polymer solution to the solvent is 1:(20-40).

[0021] As a preferred embodiment, the ultrasonic time in step 4 is 20 to 60 minutes and the temperature is room temperature.

[0022] As a preferred embodiment, the spraying condition of the spray gun in step 4 is 60 to 100 degrees Celsius; the drying condition is vacuum drying at 20 to 50 degrees Celsius for 8 to 10 hours.

[0023] The present invention also provides an application of the copper nanoparticle catalyst described in any one of the above technical solutions or the copper nanoparticle catalyst obtained by any preparation method described in the above technical solutions in the electrocatalytic reduction reaction of nitrogen monoxide.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The copper nanoparticle catalyst disclosed in the present invention has a specific structure and morphology. Under the action of the copper nanoparticle catalyst, the nano size increases the specific surface area of ​​the material, and the gaps between the particles are conducive to the diffusion of nitric oxide and ammonia, thereby achieving efficient electrocatalytic reduction of nitric oxide to ammonia.

[0026] (2) The present invention prepares the copper nanoparticle catalyst by the oleylamine oleic acid reduction method, which is convenient to prepare, has mild reaction conditions, has a large cost advantage, and is conducive to large-scale industrial application;

[0027] (3) The copper nanoparticle catalyst provided by the present invention can achieve 396.9 μmol cm in a conventional H-type electrolytic cell. -2 h -1 The ammonia Faraday efficiency is 94.78%, showing high catalytic activity and selectivity for nitric oxide to ammonia, which is suitable for the commercial application of electrocatalytic nitric oxide reduction and ammonia. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The scanning electron microscope (left) and transmission electron microscope (right) images of the copper nanoparticle catalyst obtained in Example 1 of the present invention are shown;

[0029] Figure 2The X-ray diffraction spectra of the carbon paper-based copper nanoparticle catalyst and the standard copper metal crystal obtained in Example 1 of the present invention;

[0030] Figure 3 The Faraday efficiency and ammonia production rate-potential curve of the electroreduction reaction of nitric oxide catalyzed by the copper nanoparticle catalyst of Example 4 of the present invention in an H-type electrolytic cell with an acidic electrolyte;

[0031] Figure 4 The Faraday efficiency and ammonia production rate-potential curve of the electroreduction reaction of nitric oxide catalyzed by the copper nanoparticle catalyst of Example 5 of the present invention in an H-type electrolytic cell with a neutral electrolyte;

[0032] Figure 5 This is the Faraday efficiency-current density curve of the copper nanoparticle catalyst in Example 6 of the present invention catalyzing the electroreduction reaction of nitric oxide in a flow cell. DETAILED DESCRIPTION

[0033] The present invention provides a method for preparing a copper nanoparticle catalyst, comprising the following steps:

[0034] Step 1: After mixing the copper source, oleylamine and oleic acid, heat and stir at 20 to 60 degrees Celsius for 20 to 40 minutes under nitrogen or inert atmosphere to mix evenly;

[0035] Step 2: heating the mixed solution to 160-220 degrees Celsius at a certain rate under nitrogen or inert atmosphere, and fully reacting for 2-4 hours under magnetic stirring to obtain a mixture of copper particles and other reaction products;

[0036] Step 3: After the mixed solution is allowed to stand and cool, a solvent is added, the mixture is centrifuged, washed, and dried to obtain nanostructured copper particles;

[0037] Step 4: adding a solvent and a perfluorosulfonic acid polymer solution, ultrasonicating the mixed solution, spraying the solution evenly on the carbon material with a spray gun, and obtaining a copper nanoparticle catalyst based on the carbon material after drying.

[0038] In the present invention, the copper source includes but is not limited to one or more of copper acetate, copper sulfate, copper acetylacetonate, copper carbonate and basic copper carbonate, preferably copper acetate, copper sulfate and copper acetylacetonate.

[0039] In the present invention, the molar ratio of the copper source, oleylamine and oleic acid is 1:(120-140):(12-14), preferably 1:(121-135):(12.1:13.5), and the magnetic stirring rate is 500-700 r / min, preferably 530-670 r / min, and more preferably 550-650 r / min.

[0040] In the present invention, the heating rate in step 2 is 1 to 4 degrees Celsius per minute, preferably 1.5 to 3.5 degrees Celsius.

[0041] In the present invention, the magnetic stirring rate in step 2 is 500 to 700 rpm, preferably 530 to 670 rpm, and more preferably 550 to 650 rpm.

[0042] In the present invention, the solvent added in step 3 is one or more of n-hexane, cyclohexane, n-pentane and benzene, and the volume ratio of the reaction product to the solvent is 1:3.

[0043] In the present invention, the number of centrifugation in step 3 is 2 to 6 times, preferably 3 to 5 times, the centrifugal speed is 8000 to 12000 rpm, preferably 9000 to 11000 rpm, and the centrifugal time is 6 to 10 rpm.

[0044] In the present invention, the carbon material in step 4 is preferably carbon paper.

[0045] In the present invention, the solvent in step 4 is one or more of deionized water, methanol, ethanol, and isopropanol, preferably isopropanol and ethanol.

[0046] In the present invention, the mass ratio of the catalyst to the solvent in step 4 is 1:(50-70), preferably 1:(55-65); the volume ratio of the perfluorosulfonic acid polymer solution to the solvent is 1:(20-40), preferably 1:(23:37), and more preferably 1:(25:35).

[0047] In the present invention, the ultrasonic time in step 4 is 20 to 60 minutes, preferably 30 to 50 minutes.

[0048] In the present invention, the spraying condition of the spray gun in step 4 is 60-100 degrees Celsius, preferably 70-90 degrees Celsius; the drying condition is vacuum drying at 20-50°C for 8-10 hours, preferably drying at room temperature for 8.5-9.5 hours.

[0049] The present invention also provides an application of the copper nanoparticle catalyst described in any one of the above technical solutions or the copper nanoparticle catalyst obtained by any preparation method described in the above technical solutions in the electrocatalytic reduction reaction of nitrogen monoxide.

[0050] In order to further illustrate the present invention, a copper nanoparticle catalyst provided by the present invention and its preparation method and application are described in detail below in combination with examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following examples.

[0051] Example 1

[0052] This embodiment prepares a copper nanoparticle catalyst, which specifically includes the following steps:

[0053] Step 1: Under argon atmosphere, 0.1 mmol copper acetylacetonate, 40 mL oleylamine and 4 mL oleic acid were poured into two round-bottom flasks, heated and stirred at 40 degrees Celsius for 30 minutes, with a magnetic stirring rate of 650 revolutions per minute, and uniformly mixed to obtain a mixed solution;

[0054] Step 2: heating the mixed solution to 200 degrees Celsius at a heating rate of 2 degrees Celsius per minute under an argon atmosphere, and fully reacting the mixture for 2 hours at a magnetic stirring rate of 650 revolutions per minute to obtain a mixture of copper particles and other reaction products;

[0055] Step 3: After the mixed solution is allowed to stand and cool, n-hexane is added as a solvent, and the mixture is centrifuged at a centrifugal speed of 12,000 revolutions per minute for 6 minutes. After centrifugation for 3 times, the mixture is washed and dried to obtain nanostructured copper particles;

[0056] Step 4: Take 0.06g of the obtained copper particles, pour 6mL of ethanol and 200μL of perfluorosulfonic acid polymer solution, and ultrasonicate the mixed solution at room temperature for 30min. Use a spray gun to evenly spray the ultrasonicated solution on the carbon paper fixed on the spray gun platform heated at 80℃. Vacuum dry at 40℃ for 10h to obtain a copper nanoparticle catalyst with carbon paper as the substrate.

[0057] The copper nanoparticle catalyst obtained in this example was characterized.

[0058] Figure 1 The scanning electron microscope (left) and transmission electron microscope (right) images of the copper nanoparticle catalyst obtained in this example are shown.

[0059] Figure 2 The X-ray diffraction spectra of the carbon paper-based copper nanoparticle catalyst and the standard copper metal crystal obtained in Example 1 of the present invention;

[0060] Example 2

[0061] This embodiment prepares a copper nanoparticle catalyst, which specifically includes the following steps:

[0062] Step 1: Under argon atmosphere, pour 0.25 mmol copper sulfate, 9 mL oleylamine and 0.9 mL oleic acid into two round-bottom flasks, heat and stir at 25 degrees Celsius for 30 minutes, and magnetically stir at a rate of 600 revolutions per minute to obtain a mixed solution after uniform mixing;

[0063] Step 2: heating the mixed solution to 220 degrees Celsius at a heating rate of 2 degrees Celsius per minute under an argon atmosphere, and fully reacting the mixture for 3 hours at a magnetic stirring rate of 650 revolutions per minute to obtain a mixture of copper particles and other reaction products;

[0064] Step 3: After the mixed solution is allowed to stand and cool, n-pentane is added as a solvent, and the mixture is centrifuged at a centrifugal speed of 10,000 revolutions per minute for 6 minutes. After centrifugation for 3 times, the mixture is washed and dried to obtain nanostructured copper particles;

[0065] Step 4: Take 0.06g of the obtained copper particles, pour 6mL of ethanol and 200μL of perfluorosulfonic acid polymer solution, and ultrasonicate the mixed solution at room temperature for 20 minutes. Use a spray gun to evenly spray the ultrasonicated solution on a carbon paper fixed on a spray gun stand heated at 70 degrees Celsius. Vacuum dry at 40 degrees Celsius for 10 hours to obtain a copper nanoparticle catalyst with carbon paper as the substrate.

[0066] Example 3

[0067] This embodiment prepares a copper nanoparticle catalyst, which specifically includes the following steps:

[0068] Step 1: Under argon atmosphere, 0.1 mmol of copper acetate, 35 mL of oleylamine and 3.5 mL of oleic acid were poured into two round-bottom flasks, heated and stirred at 30 degrees Celsius for 40 minutes, with a magnetic stirring rate of 650 revolutions per minute, and uniformly mixed to obtain a mixed solution;

[0069] Step 2: heating the mixed solution to 160 degrees Celsius at a heating rate of 2 degrees Celsius per minute under an argon atmosphere, and fully reacting the mixture for 4 hours at a magnetic stirring rate of 700 revolutions per minute to obtain a mixture of copper particles and other reaction products;

[0070] Step 3: After the mixed solution is allowed to stand and cool, n-hexane is added as a solvent, and the mixture is centrifuged at a centrifugal speed of 12,000 revolutions per minute for 10 minutes. After centrifugation for 4 times, the mixture is washed and dried to obtain nanostructured copper particles;

[0071] Step 4: Take 0.03g of the obtained copper particles, pour 3mL of ethanol and 90μL of perfluorosulfonic acid polymer solution, and ultrasonicate the mixed solution at room temperature for 40 minutes. Use a spray gun to evenly spray the ultrasonicated solution on a carbon paper fixed on a spray gun stand heated at 70 degrees Celsius. Vacuum dry at 30 degrees Celsius for 10 hours to obtain a copper nanoparticle catalyst with carbon paper as the substrate.

[0072] Example 4

[0073] Catalytic performance testing of copper nanoparticle catalysts.

[0074] The catalytic performance of the nitric oxide electroreduction reaction was tested using a copper nanoparticle catalyst prepared in Example 1 of the present invention.

[0075] The carbon paper loaded with the copper nanoparticle catalyst obtained in Example 1 of the present invention was used as the working electrode, platinum was used as the counter electrode, and the silver / silver chloride electrode was used as the reference electrode. A 0.1M / L hydrochloric acid solution and a 4mol / L potassium hydroxide solution were used as the cathode electrolyte and the anode electrolyte, and the nitric oxide electroreduction performance test was carried out in an H-type electrolytic cell. During the test, the nitric oxide flow rate was maintained at 30sccm. The test adopted a constant voltage method, and the applied voltage range was -0.05V to -1.55V (relative to the reversible hydrogen electrode). The reaction product ammonia was dissolved in the cathode electrolyte, and the coulomb amount corresponding to the product concentration was calculated by ion chromatography. The total coulomb amount recorded by the electrochemical workstation was used to obtain the data of catalytic selectivity, activity, etc.

[0076] Figure 3 The Faraday efficiency and ammonia production rate-potential curve of the copper nanoparticle catalyst obtained in Example 1 for catalyzing the electroreduction reaction of nitric oxide in an H-type electrolytic cell with an acidic cathode electrolyte. It can be seen that under different tested cathode potentials, the copper nanoparticle catalyst obtained in this example exhibits a good ammonia production rate, and reaches a Faraday efficiency of 94.78% and a potential of 396.9 μmol cm at -0.95 V. -2 h -1 The ammonia production rate is 2.5 times that of the raw materials, achieving a high selectivity for nitric oxide to ammonia.

[0077] Example 5

[0078] Catalytic performance testing of copper nanoparticle catalysts.

[0079] The catalytic performance of the nitric oxide electroreduction reaction was tested using a copper nanoparticle catalyst prepared in Example 1 of the present invention.

[0080] The carbon paper loaded with the copper nanoparticle catalyst obtained in Example 1 of the present invention was used as the working electrode, platinum was used as the counter electrode, and the silver / silver chloride electrode was used as the reference electrode. A 0.25M / L lithium sulfate solution and a 4mol / L potassium hydroxide solution were used as the cathode electrolyte and the anode electrolyte, and the nitric oxide electroreduction performance test was carried out in an H-type electrolytic cell. During the test, the nitric oxide flow rate was maintained at 30sccm. The test adopted a constant voltage method, and the applied voltage range was 0V to -2.4V (relative to a reversible hydrogen electrode). The reaction product ammonia was dissolved in the cathode electrolyte, and the coulomb amount corresponding to the product concentration was calculated by ion chromatography. The total coulomb amount recorded by the electrochemical workstation was used to obtain the data of catalytic selectivity, activity, etc.

[0081] Figure 4The Faraday efficiency and ammonia production rate-potential curve of the copper nanoparticle catalyst obtained in Example 1 catalyzing the electroreduction reaction of nitric oxide in an H-type electrolytic cell with a neutral cathode electrolyte are shown. It can be seen that under different tested cathode potentials, the copper nanoparticle catalyst obtained in this example still exhibits good catalytic efficiency in a neutral electrolyte.

[0082] Example 6

[0083] Catalytic performance testing of copper nanoparticle catalysts.

[0084] The catalytic performance of the nitric oxide electroreduction reaction was tested using a copper nanoparticle catalyst prepared in Example 1 of the present invention.

[0085] The carbon paper loaded with the copper nanoparticle catalyst obtained in Example 1 of the present invention was used as the working electrode, platinum was used as the counter electrode, and the silver / silver chloride electrode was used as the reference electrode. A 0.1M / L hydrochloric acid solution was used as the cathode electrolyte and the anode electrolyte to test the nitric oxide electroreduction performance in a flow cell. During the test, the nitric oxide flow rate was maintained at 30 sccm and the electrolyte flow rate was maintained at 1.8 ml / min. The test adopted a constant current method, and the applied current density range was -30 to -800 mA cm -2 The reaction product ammonia is dissolved in the electrolyte and detected by ion chromatography. The coulomb amount corresponding to the product concentration is calculated, and the catalytic selectivity, activity and other data are obtained based on the total coulomb amount recorded by the electrochemical workstation.

[0086] Figure 5 This is the Faraday efficiency-current density curve of the copper nanoparticle catalyst obtained in Example 1 catalyzing the electroreduction reaction of nitric oxide in a flow cell. It can be seen that under different test current densities, the copper nanoparticle catalyst obtained in this example exhibits a good ammonia production rate.

[0087] The above embodiments are merely descriptions of preferred implementations of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solution of the present invention by ordinary personnel in the field should fall within the protection scope of the present invention. The technical contents for which protection is sought in the present invention have all been recorded in the claims.

Claims

1. A copper nanoparticle catalyst is used for the electrocatalytic reduction reaction of nitric oxide, characterized in that: The copper nanoparticle catalyst is in the form of dispersed particles with a particle size of 20 to 80 nanometers. The preparation method of the copper nanoparticle catalyst comprises the following steps: Step 1: After mixing copper salt, oleylamine and oleic acid, heat and stir at 20-60 degrees Celsius for 20-40 minutes under nitrogen or inert atmosphere to uniformly mix, the copper salt includes one or more of copper acetate, copper sulfate, copper acetylacetonate, copper carbonate and basic copper carbonate, and the molar ratio of copper salt, oleylamine and oleic acid is 1: (120-140): (12-14), and magnetic stirring is used at a speed of 500-700 revolutions per minute; Step 2: The mixed solution is heated to 160-220 degrees Celsius at a certain rate under nitrogen or inert atmosphere, and fully reacted for 2-4 hours under magnetic stirring to obtain a mixed solution of copper particles and other reaction products, the heating rate is 1-4 degrees Celsius per minute, and the magnetic stirring rate is 500-700 revolutions per minute; Step 3: After the mixed solution is allowed to stand and cool, a solvent is added, the mixture is centrifuged, washed, and dried to obtain nanostructured copper particles; Step 4: Add solvent and perfluorosulfonic acid polymer solution to the nanostructured copper particles, ultrasonicate the mixed solution, spray the solution evenly on the carbon material with a spray gun, and obtain a copper nanoparticle catalyst with the carbon material as the base after drying.

2. The copper nanoparticle catalyst according to claim 1 is applied to the electrocatalytic reduction reaction of nitric oxide, characterized in that: The solvent added in step 3 is one or more of n-hexane, cyclohexane, n-pentane and benzene, and the volume ratio of the mixed solution to the solvent is 1:

3.

3. The copper nanoparticle catalyst according to claim 1 is applied to the electrocatalytic reduction reaction of nitric oxide, characterized in that: In step 3, the number of centrifugation is 2 to 6 times, the centrifugal speed is 8000 to 12000 revolutions per minute, and the centrifugal time is 6 to 10 minutes.

4. The copper nanoparticle catalyst according to claim 1 is applied to the electrocatalytic reduction reaction of nitric oxide, characterized in that: In step 4, the carbon material is carbon cloth or carbon paper.

5. The copper nanoparticle catalyst according to claim 1 is applied to the electrocatalytic reduction reaction of nitric oxide, characterized in that: In step 4, the solvent is one or more of deionized water, methanol, ethanol, and isopropanol, the mass ratio of the nanostructured copper particles to the solvent is 1: (50-70), and the volume ratio of the perfluorosulfonic acid polymer solution to the solvent is 1: (20-40).

6. The copper nanoparticle catalyst according to claim 1 is applied to the electrocatalytic reduction reaction of nitrogen monoxide, characterized in that: In step 4, the ultrasonic time is 20 to 60 minutes, and the temperature is room temperature; the temperature during spraying with the spray gun is 60 to 100 degrees Celsius; and the drying condition is vacuum drying at 20 to 50 degrees Celsius for 8 to 10 hours.

Citation Information

Patent Citations

  • Method for manufacturing copper nanoparticles and copper nanoparticles manufactured using the same

    CN101161380A

  • High-grain-boundary-density elemental copper nanoparticle catalyst as well as preparation method and application thereof

    CN114918423A